Extraordinary Bodies, Invisible Worlds: Somatic Pedagogy in Neo-pagan Ritual Practices - Dansac, Yael (Approaching Religion, 2024)
Numerous scholars have signalled that neo-pagan practitioners use their body and their senses to interact with the divine and elaborate a spiritual experience. However, the learning process followed to achieve and produce a sensing body capable of communicating with summoned entities has not been properly assessed, until very recently. For over a decade, I have conducted ethnographic research on neo-pagan ritual practices held at European megalithic sites to understand how practitioners learn to co-construct their somatic experiences culturally. Collected data allowed me to develop a model I called somatic pedagogy, which is a progressive sensory learning process applied by ritual specialists organizing practices. In this review article, I present a synthesis of published material where I have developed this model extensively. Specifically, I will go through the elements that permit this kind of somatic education to be implemented within analysed practices: the specificities of neo-pagan ontologies about the human body and world, the potential of neo-pagan rituals to function as learning sites, and the main stages of this progressive bodily education